2001
DOI: 10.1124/mol.59.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Two Nuclear Proteins, Cin5 and Ydr259c, Confer Resistance to Cisplatin inSaccharomyces cerevisiae

Abstract: In an attempt to identify genes that can confer resistance to cisplatin, we introduced a yeast genomic library into Saccharomyces cerevisiae and selected for transformants that grew in the presence of a normally toxic concentration of cisplatin. Plasmids were rescued from the transformants and were analyzed for the presence of individual open reading frames that conferred resistance to cisplatin. We isolated two genes, CIN5 and YDR259c, that increased resistance to cisplatin when overexpressed in Saccharomyces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 17 publications
1
47
1
Order By: Relevance
“…The fact that YAP4 is responsive to such a wide plethora of environmental insults suggests an important role in the response to stress. Indeed, previous work has revealed that its overexpression is capable of relieving cellular sensitivity to a wide range of conditions and drugs, including salt (Mendizabal et al, 1998;Nevitt et al, 2004), cisplatin (Furuchi et al, 2001) and quinoline ringcontaining antimalarial drugs (Delling et al, 1998). The fact that the adduct-forming chemotherapeutic agent cisplatin acts at the level of transcriptional repression, by denying the RNA polymerase II initiation complex access to the TATA box (Vichi et al, 1997), may suggest a role for Yap4p within the realm of the basal transcriptional machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that YAP4 is responsive to such a wide plethora of environmental insults suggests an important role in the response to stress. Indeed, previous work has revealed that its overexpression is capable of relieving cellular sensitivity to a wide range of conditions and drugs, including salt (Mendizabal et al, 1998;Nevitt et al, 2004), cisplatin (Furuchi et al, 2001) and quinoline ringcontaining antimalarial drugs (Delling et al, 1998). The fact that the adduct-forming chemotherapeutic agent cisplatin acts at the level of transcriptional repression, by denying the RNA polymerase II initiation complex access to the TATA box (Vichi et al, 1997), may suggest a role for Yap4p within the realm of the basal transcriptional machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only Yap 4 and 6, when over-expressed, confer CDDP resistance (18). (ii) Yap4 targets the largest number of genes and Yap1 is epistatic to the largest number of genes in both DNA damaging conditions combined.…”
Section: Discussionmentioning
confidence: 99%
“…As many as five Yaps (1, 2, 4, 5, and 6) have been implicated in the cellular response to methylmethanesulfonate (MMS), a DNA alkylating agent (12)(13)(14)(15)(16), and cis-diamminedichloroplatinum (CDDP), a DNA cross-linking agent (17,18). With regard to other stresses, Yap TFs carry out overlapping but distinct biological functions with Yap1 being the major player in oxidative stress, Yap2 in cadmium stress, Yap4 and Yap6 in osmotic stress, and Yap8 in arsenic stress (5,19).…”
mentioning
confidence: 99%
“…YAP6 encodes a transcription factor homologous to YAP1p (basic leucine zipper, yeast homolog of c-Jun). Overexpression of YAP6 increases resistance to cisplatin (23), one of the most widely used drugs for cancer chemotherapy. The LA-scouting leaders are often found to scout each other.…”
Section: Longevitymentioning
confidence: 99%